Report of Erpetogomphus sabaleticus Williamson, 1918 (Odonata: Gomphidae) feeding on Diaphorina citri Kuwayama (Hemiptera: Liviidae) - Kondo, Takumasa; Palacino Rodrıguez, Fredy; Peña Cuellar, Richard Danilo (Universidad del Valle, 2025)
The dragonfly Erpetogomphus sabaleticus Williamson, 1918 (Odonata: Anisoptera: Gomphidae) is for the first time reported preying on Diaphorina citri Kuwayama (Hemiptera: Liviidae). A compiled list of more than 63 species distributed in seven orders and seventeen families of arthropod (insects and spiders) natural enemies of D. citri is provided.